Diminished Learning Over Repeated Exposures (LORE) in preclinical Alzheimer's disease. Issue 1 (5th January 2021) - Samaroo, Aubryn; Amariglio, Rebecca E.; Burnham, Samantha; Sparks, Paige; Properzi, Michael; Schultz, Aaron P.; Buckley, Rachel; Johnson, Keith A.; Sperling, Reisa A.; Rentz, Dorene M.; Papp, Kathryn V.
Abstract: Introduction: We determine whether diminished Learning Over Repeated Exposures (LORE) identifies subtle memory decrements in cognitively unimpaired (CU) older adults with Alzheimer's disease (AD) biomarker burden. Methods: Ninety‐four CU participants (mean age = 77.6 ± 5.02) completed a challenging associative memory test, at home, monthly, for up to 1 year (mean = 9.97 months) on a study‐issued iPad. Learning curves for face‐name memory were computed for two versions completed monthly: same face‐name pairs (A‐A‐A) and alternate face‐name pairs (B‐C‐D). Positron emission tomography (PET) imaging characterized global amyloid (Pittsburgh Compound‐B (PiB); amyloid beta (Aβ)+/−) and regional tau burden (flortaucipir). Results: Diminished LORE for same (but not alternate) face‐name pairs was associated with greater amyloid and tau burden. Aβ+/− group differences for same face‐name pairs emerged by the fourth exposure and was of medium‐to‐large magnitude (Cohen's d = 0.66; 95% confidence interval [CI] = 0.25‐1.08). Discussion: Subtle decrements in learning related to AD pathological burden in CU are detectable over short time‐intervals (ie, months). Implications for prevention trial design are discussed.